2019
DOI: 10.2166/wst.2019.433
|View full text |Cite
|
Sign up to set email alerts
|

Removal efficiency of Gram-positive and Gram-negative bacteria using a natural coagulant during coagulation, flocculation, and sedimentation processes

Abstract: Staphylococcus sp. as Gram-positive and Escherichia coli as Gram-negative are bacterial pathogens and can cause primary bloodstream infections and food poisoning. Coagulation, flocculation, and sedimentation processes could be a reliable treatment for bacterial removal because suspended, colloidal, and soluble particles can be removed. Chemical coagulants, such as alum, are commonly used. However, these chemical coagulants are not environmentally friendly. This present study evaluated the effectiveness of coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Another study evaluated the effectiveness of coagulation processes in eliminating Staphylococcus and E. coli by using diatomite. The results proved a significant removal of 85.61% (Sha'arani et al, 2019).…”
Section: Treatment Processes For the Removal Of Argmentioning
confidence: 80%
“…Another study evaluated the effectiveness of coagulation processes in eliminating Staphylococcus and E. coli by using diatomite. The results proved a significant removal of 85.61% (Sha'arani et al, 2019).…”
Section: Treatment Processes For the Removal Of Argmentioning
confidence: 80%
“…On the other hand, each module of the water treatment system carries out processes with properties that reduce the number of microorganisms. The use of coagulation, flocculation, and sedimentation is usually one of the first stages of water treatment, which contributes to mechanically 'trapping' some of the bacteria in the solid fraction [44]. As noted by Xiangli et al the implementation of coagulation prior to the use of full-scale ultrafiltration is an effective method in the production of drinking water [45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a constant search for improved coagulants, especially on the use of coagulants derived from natural sources (i.e., chitosan, Moringa oleifera , diatomite) and laboratory scale studies were conducted to identify the optimal coagulant dose for various applications. Diatomite (1.0–2.5 mg/L) added to 50 NTU turbid water during sedimentation stage produced 0.87 log reduction of E. coli at pH 5 (Sha'arani et al, 2019). While the laboratory scale studies have shown promising results, the fact that need for conducting detailed study to identify an optimal coagulant dosage has limited the deployment of new types of coagulants for the market due to the need for involvement of an expert in the field rather than a technology managed by non‐experts.…”
Section: Laboratory Scale and Pre‐commercialized Water Treatment Solu...mentioning
confidence: 99%